1927 Mich. Pub. Acts 891, No. 372, § 11. - (:unkn) unknown (General Publisher, 1927)
No person shall wilfully alter, remove, or obliterate the. name of the maker, model, manufacturer's number, or other identity mark of any pistol
--
Keywords: DEFACED FIREARMS